2018
DOI: 10.1177/0954408918787098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of the surface waviness in the single-point incremental sheet metal forming

Abstract: Presence of waviness in the incremental sheet forming has a detrimental effect on the surface quality of parts, especially on the appearance of those covered with paint. In this paper, the effects of tool diameter, feed rate, spindle speed, and vertical step have been studied on the surface waviness using an innovative method. The proposed method is based on the root mean square deviation of the height of the points located on the wavy surface. In this way, some points are selected on the formed wall and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…During the SPIF, when the tool moves on the sheet, certain areas on the blank remain as unforced regions because of the helical path of tool movement. Therefore, these sections lead to the surface waviness [22]. In addition, tool movement in a local zone on the blank during the SPIF results in the surface roughness.…”
Section: -Methods Of the Surface Roughness Measurementmentioning
confidence: 99%
“…During the SPIF, when the tool moves on the sheet, certain areas on the blank remain as unforced regions because of the helical path of tool movement. Therefore, these sections lead to the surface waviness [22]. In addition, tool movement in a local zone on the blank during the SPIF results in the surface roughness.…”
Section: -Methods Of the Surface Roughness Measurementmentioning
confidence: 99%
“…The waviness of the items' treated surfaces, as well as their roughness and shape accuracy, all have a substantial effect on their service reliability [39]. As seen in Figure 7(b), waviness is a surface imperfection with a wavelength larger than the roughness [40]. Alternatively, surface waviness refers to low frequency imperfections on a surface that are overlaid with surface roughness [41].…”
Section: Surface Wavinessmentioning
confidence: 99%
“…Ham et al [3] carried out the influence of the diameter of the forming tool head on the surface quality of the forming part, and the study showed that under the condition of constant layer feed, the residual height between two adjacent layers' trajectories gradually increased with the decrease of the diameter of the tool head. Mohammad et al [4] conducted an experimental study on the process parameters affecting the surface corrugations of progressive forming parts. The study showed that the layer feed rate and tool head radius had a great influence on the surface corrugations of parts, while the feed speed and spindle speed had little influence.…”
Section: Introductionmentioning
confidence: 99%